ANALISIS POTENSI EKONOMI DAN KELAYAKAN USAHA BUDIDAYA IKAN BANDENG (Chanos chanos) DESA TAMBUHA KECAMATAN WATUNOHU, KOLAKA UTARA - Syamsuri Syamsuri; Hasria Alang (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
Analysis of economic potential and business feasibility is intended so that the actors can avoid the risk of loss, one of which is in the milkfish cultivation business. Generally, milkfish cultivation in Indonesia is carried out in brackish or greedy water. One area that also does this cultivation is Tambuha Village. The purpose of this research is to see the economic potential and future of milkfish cultivation business in Tambuha Village. The research method is descriptive. The research variables are economic potential and business behavior. Data was collected randomly through observation and interviews with informants. Data analysis was carried out qualitatively to see the description of the cultivation business in the research location, and quantitatively to determine the economic potential and business feasibility. Economic potential analysis is carried out through revenue and income analysis, while business feasibility is analyzed using the operating profit (OP) formula, benefit cost ratio (BCR), payback period (PP), profitability, break-even point (BEP), return of investment (ROI). The results showed that the milkfish cultivation business in Tambuha Village has economic potential because it can be profitable. In addition, this business is also very feasible because it is based on the value of OP, BRC, PP, BEP and ROI.